Exploring farmers attitude, practice and relationship with adoption of improved pearl millet technology in north-eastern Nigeria - Galadima, Mohammed; Hassan, Salim; Man, Norsida; Abu, Ibrahim Abdul (IJSTR, 2019)
In Sub-Sahara Africa, Nigeria is one of the major pearl millet producing country with an average annual production of 4.8 million tons. Nevertheless, Pearl millet farming is mostly carried out in the North-eastern Nigeria. Although, the productivity is very low, resulting to low level of growers attitude and practices on the improved technologies despite all the efforts of the extension agents and the stakeholders in the region to improve the situation. Hence, growers in North-eastern Nigeria mostly rely on traditional method of production and this has created a gap for need of this study. Thus, this study is designed to explore on farmers attitude, practice and relationship with adoption of improved pearl millet technologies in the region. Purposive sampling techniques was used to select 3 states and 9 local governments areas that are actively involved in pearl millet farming. Stratified random and systematic sampling technique was used to select 477 pearl millet growers. Information were collected using a self-report validated questionnaire. Descriptive, Pearson Moment Correlation and Multiple linear-regression models were employed to analyze the data. From the findings, respondents level of attitude was moderate, practice and adoption were at higher level. It was also observed that significant relationship existed between attitude, practice at (p<0.01) towards adoption of improved pearl millet technologies. Regression results revealed that practice is a significant contributor to adoption. while, attitude did not contribute. The study suggests that, Pearl millet growers should be encouraged through government policies and strategies that focused on the development of positive attitude towards adoption of improved pearl millet technologies and subsequent increase in the farmers level of output and other relevant areas of improvement among growers in North-eastern Nigeria.